Reputation of Moroccan universities: adoption and adaptation of strategic and marketing communication case of Abdelmalek Essaâdi and Hassan 1st - Drouiche , Laila; Baha , Hassan (Cadernos de Educação Tecnologia e Sociedade, 2024)
The competitive environment requires universities to develop and maintain their reputations. The importance of university reputation as a strategic intangible asset has also grown over the past two decades. Although there are studies in the literature that attempt to develop university reputation strategies, they are still in their infancy. The present project attempts to measure the reputation of Moroccan universities by adopting a qualitative methodology, through a review of relevant literature and a documentary analysis of universities' digital interfaces. University reputation is developed and validated through analysis of data extracted from web portals and social networks. The results show that a university's reputation is a multidimensional concept comprising dimensions such as academic competence, institutional mastery and socio-economic attractiveness. The aim of this research is to enrich the literature on university reputation, enabling academics and practitioners to assess the reputation of different universities.